Morality and political violence - Coady, C. A. J. (Cambridge University Press, 2008)
"Political violence in the form of wars, insurgencies, terrorism, and violent rebellion constitutes a major human challenge today as it has so often in the past. It is a challenge not only to life and limb, but also to morality itself. In this book, C.A.J. Coady brings a philosophical and ethical perspective to the subject. He places the problems of war and political violence in the frame of reflective ethics. In clear and accessible language, Coady reexamines a range of urgent problems pertinent to political violence against the background of a contemporary approach to just war thinking. The problems examined include the right to make war, the right way to conduct war, terrorism, revolution, humanitarianism, mercenary warriors, conscientious objection, combatant and noncombatant status, the ideal of peace and the right way to end war, pacifism, weapons of mass destruction, and supreme emergency exemptions from just war prohibition. Coady attempts to vindicate the relevance of the just war tradition to conternporary problems without applying the tradition in a merely mechanical or uncritical fashion."--Jacket